Remaking Tank Man, in China - Hillenbrand, M (SAGE Publications, 2017)
Tank Man, the image of the lone protestor who faced down the tanks near Tian’anmen Square in 1989, leads a vibrant afterlife in political cartoons, memes, and YouTube remixes. In an era when staying memorable increasingly means being searchable online, these digital remakes have helped to keep his image fresh – outside China anyway. In China itself, though, Tank Man is a famously verboten image, mostly policed out of online sight. The digital artists who have repurposed his image are typically so harried by the censors that their work cannot hope to endow Tank Man with mass viral visibility, let alone the iconic status he possesses abroad. But precisely because of their fugitive character – which produces audiences who are alert, amused, and on the qui vive – these repurposings ensure that Tank Man remains the grit in the clam of public secrecy about 1989.